Spatiotemporal Gait Parameters in Community-Dwelling Old-Old Koreans: Impact of Muscle Mass, Physical Performance, and Sarcopenia - Youngyun Jin; Taewan Kim; Donghyun Kim; Young-Min Park; Jinkyung Cho (Applied Sciences)
Muscle mass and physical function are key risk factors for sarcopenia, with emerging evidence suggesting links to gait variability in older adults. This study investigated the relationships between muscle mass decline, poor physical performance, sarcopenia, and spatiotemporal gait parameters in 242 Korean older adults (mean age: 79.1 ± 4.2 years). Muscle mass (MM) was measured via dual-energy X-ray absorptiometry (DXA), physical performance (PP) via the Short Physical Performance Battery (SPPB), and gait parameters (gait speed, stride length, double-limb stance) via the Optogait® system. Stride length significantly influenced low MM, while double-limb stance was linked to increased risks of poor PP and sarcopenia. The area under the curve (AUC) for double-limb stance was 0.698 (95% CI: 0.633–0.763, p < 0.001) for poor PP and 0.647 (95% CI: 0.568–0.726, p = 0.001) for sarcopenia. A novel model combining gait speed and double-limb stance achieved an AUC of 0.702 (95% CI: 0.622–0.781, p < 0.001) with 78.9% sensitivity and 76.3% specificity. These findings highlight spatiotemporal gait analysis as a promising tool for early sarcopenia detection and management in older adults.